Attitude Toward and Propensity to Engage in Unethical Behavior: Measurement Invariance across Major among University Students - Chen, Yuh-Jia (Journal of business ethics, 2006)
This research examines business and psychology students’ attitude toward unethical behavior (measured at Time 1) and their propensity to engage in unethical behavior (measured at Time 1 and at Time 2, 4 weeks later) using a 15-item Unethical Behavior measure with five Factors: Abuse Resources, Not Whistle Blowing, Theft, Corruption, and Deception. Results suggested that male students had stronger unethical attitudes and had higher propensity to engage in unethical behavior than female students. Attitude at Time 1 predicted Propensity at Time 1 accurately for all five factors (concurrent validity): If students consider it to be unethical, then, they are less likely to engage in that unethical behavior. Attitude at Time 1 predicted only Factor Abuse Resources for Propensity at Time 2. Propensity at Time 1 was significantly related to Propensity at Time 2. Attitude at Time 1, Propensity at Time 1, and Propensity at Time 2 had achieved configural and metric measurement invariance across major (business vs. psychology). Thus, researchers may have confidence in using these measures in future research.